(untitled) (Research, Society and Development, 2021)
A health fair is established as an instrument in the learning process, where it is possible to experience different creative methodologies from a space that makes it possible to explore and share knowledge. In this study, experiences from two editions (December / 2018 and March / 2019) of an interactive fair as technology in health, experienced by volunteer and scholarship students, inserted in university programs of extension and technological initiation are reported. They were held in a Higher Education Center, divided into four sequential stations with the public interacting between them. For the dynamics, microscopes, slides, posters, models and board games were used. In the first season, the most prevalent parasites in the Center (from previous research) were characterized, with visualization of parasitic forms; in the second, symptoms of the enteroparasitoses in question were presented; in the third, models with the parasitic cycles involved, mechanisms of infection and means of prevention. The fourth, on the other hand, was a board game containing contextualized questions from previous seasons. A quiz was used, with questions converted into a game with punctuation, interaction and ranking (monitoring of pre and post course knowledge). With the fairs, it was perceptible to observe that health education actions, when well planned, have significant effects and achieve the goals of their achievements.